Nursing the cure: A phonetic analysis of /ʊə/ in South African English - Bekker, Ian (Stellenbosch Papers in Linguistics Plus, 2014)
This article is focused on providing the results of a partially impressionistic and partially acoustic phonetic analysis of the CURE vowel (i.e. /ʊə/ as in cure, tour, sure) in South African English (SAfE) and, in particular, in the main first-language (L1) sociolect of this Southern Hemisphere variety, General SAfE. While the results confirm a high degree of variability in terms of the realisation of CURE in General SAfE, a couple of trends are identifiable. Firstly, while other non-rhotic varieties of English have undergone (or are undergoing) the Second FORCE Merger, whereby CURE merges with /oː/ (e.g. cure is pronounced [kjoː]), it would appear that the Second FORCE Merger has been arrested in the General SAfE of the recorded subjects (contra certain pronouncements in the extant literature and limited to some of the subjects and certain lexical items such as sure). Secondly, in word-internal position, CURE is inclined towards smoothing (and in some cases full monophthongisation) with the quality of the resultant vowel mostly dependent on the preceding consonant. After a palatal or palato-alveolar segment in word-internal position, there appears to be a partial merger with rounded, fronted SAfE NURSE (i.e. [øː]), e.g. insurance is pronounced [ɪnʃøːɹəns]. In the case of non-post-palatal, word-internal CURE, however, the smoothed realisations are further back in phonetic space. In word-final position, the trend is for CURE to be realised as canonical [ʊə]. Generally, however, the presence in some cases of NURSE-like values in word-final position, particularly after palatal or palato-alveolar contexts (e.g. [məʧøː] for mature), as well as both the high degree of variability in the data overall and residual [oː]-realisations, point to processes of phonologisation and lexicalisation of both NURSE-like and other qualities, thus creating a large number of exceptions to the overall allophonic patterning in the data.